Pengaruh Latihan Peregangan Perut Terhadap Karakteristik Nyeri Menstruasi Remaja Awal - Andi Saifah (Faletehan Health Journal, 2020)
Menstrual pain tends to interfere with daily activities and academic appearance in teenage girls. Stretching exercise is one of the nonpharmacological interventions in dealing with pain. The main purpose of this research was to analyze the effect of abdominal stretching exercise on the characteristics of painful menstruation in early adolescents at SMP Negeri Subdistrict of Palu City. The design of this study was a quasi-experimental pre-test and post-test design. The sample was obtained by using purposive sampling with 41 respondents involved (between 12-14 years old with painful menstruation) for the treatment group and control group. The instrument used in this study was a questionnaire, characteristics of painful menstrual checklist and exercise guide booklet. Statistic test used the Wilcoxon test by 95% of a significant level. The Wilcoxon test shows that are significant difference on duration and radiation of painful menstruation before and after abdominal stretching. There is no significant difference in rhythm and menstruation painful quality (ρ> 0.05). Based on the result, it can be concluded that abdominal stretching exercises affect the decrease of duration and radiation of painful menstruation, it has not yet an effect on rhythm and menstruation painful quality.